NATIONAL AND INTERNATIONAL ECONOMIC INTERESTS - N. Gotskay (Вестник университета)
The article is devoted to questions of formation and development of national and international economic interests and their impact on the development of global economic relations. The development of multicultural interests is seen as a natural and inevitable result of the development of division of labor. National economic interests are considered as a set of objective economic needs of an independent country, the satisfaction of which ensures effective functioning and sustainable development of economic system of the country.